Students’s Civic Disposition through Learning Civics and Pedagogical Competences of High School Teachers - L. Lonto, Apeles (International Journal of Psychosocial Rehabilitation, 2020)
This paper contains research on the influence of civics teaching and the pedagogical competence of teachers on the development of students’ civic dispositions. The main problem in this research is: Do civics learning and pedagogical competence of teachers influence the development of civic dispositions of students in SMA Negeri 1 Kawangkoan? The data were obtained through a questionnaire distributed to 60 students. This research also involves the collection and analysis of quantitative data. The study found that: First, civics learning has a positive influence on the civic disposition of students in SMAN 1 Kawangkoan, which means that through civics learning, students could develop their civic dispositions. Second, teachers’ pedagogic competence has a positive effect on the civic disposition of students in SMAN 1 Kawangkoan. It means that the better the pedagogical competence of teachers, the higher the students’ civic dispositions. Third, civics learning and pedagogical competence of teachers jointly have a positive effect on civic dispositions students in SMAN 1 Kawangkoan. It means that through Civics teaching materials studied by students and pedagogical competence of teachers, Civic disposition of students is higher. Thus, this study recommends further research on other civic competences.